The Gut Microbiota: Master of Puppets Connecting the Epidemiology of Infectious, Autoimmune, and Metabolic Disease - Larsen, Olaf F. A.; van der Grint, Maike; Wiegers, Cato; van de Burgwal, Linda H. M. (Frontiers in Microbiology, 2022)
Infectious, autoimmune, and metabolic diseases put an enormous pressure on both quality of life and the economy. As a dysbiosis of the gut microbiota is known to negatively impact our response to all three disease types, it is of utmost importance to prevent gradual irreversible losses of beneficial microbes within this ecosystem. As such, epidemiological trends of these disease types may serve as proxies for the integrity of the human gut microbiota. Here, we present incidence data covering the last decades for prototypical infectious diseases (tuberculosis and measles), autoimmune disorders (type-1 diabetes and multiple sclerosis), and the prevalence of metabolic syndrome. Our data show that vaccination programs have led to very low incidence levels of prototypical infectious diseases. However, autoimmune and metabolic disorders are, together with the usage of antibiotics, steeply on the rise. These data suggest that the status of the gut microbiota is persistently deteriorating, as reflected by the proxies. As such, these epidemiological trends may serve as a first starting point for a mechanistic understanding of the interplay between these different disease types that can be used for future prevention and mitigation strategies.